High-resolution measurement of the time-modulated orbital electron capture and of the β+ decay of hydrogen-like 142Pm60+ ions - Kienle, Paul; Bosch, F.; Bühler, P.; Faestermann, T.; Litvinov, Yuri A.; Winckler, N.; Sanjari, M. S.; Shubina, Daria; Atanasov, Dinko; Geissel, H.; Ivanova, V.; Yan, X. L.; et al. (Physics letters, 2013)
The periodic time modulations, found recently in the two-body orbital electron capture (EC) decay of both, hydrogen-like 140Pr58+ and 142Pm60+ ions, with periods near to 7 s and amplitudes of about 20%, were re-investigated for the case of 142Pm60+ by using a 245 MHz resonator cavity with a much improved sensitivity and time resolution. We observed that the exponential EC decay is modulated with a period T=7.11(11) s, in accordance with a modulation period T=7.12(11) s as obtained from simultaneous observations with a capacitive pick-up, employed also in the previous experiments. The modulation amplitudes amount to aR=0.107(24) and aP=0.134(27) for the 245 MHz resonator and the capacitive pick-up, respectively. These new results corroborate for both detectors exactly our previous findings of modulation periods near to 7 s, though with distinctly smaller amplitudes. Also the three-body β+ decays have been analyzed. For a supposed modulation period near to 7 s we found an amplitude a=0.027(27), compatible with a=0 and in agreement with the preliminary result a=0.030(30) of our previous experiment. These observations could point at weak interaction as origin of the observed 7 s-modulation of the EC decay. Furthermore, the data suggest that interference terms occur in the two-body EC decay, although the neutrinos are not directly observed.